2007
DOI: 10.1007/s00431-007-0432-0
|View full text |Cite
|
Sign up to set email alerts
|

Interchangeability of a hepatitis A vaccine second dose: Avaxim 80 following a first dose of Vaqta 25 or Havrix 720 in children in Turkey

Abstract: All three vaccines are safe and highly immunogenic in healthy children aged 1 to 15 years. Avaxim 80 may also be given as the second dose when Havrix 720 or Vaqta 25 are given as the first dose. The pattern of seroprevalence seen here is similar to that reported in a number of recent evaluations in Turkey, and are supportive of the routine hepatitis A vaccination of young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…A large number of studies have been reported mainly from Turkey and Iran. The overall prevalence rate reported in different provinces of Turkey during the past 10 years among young adults (≤19 years old) ranges between 13% and 64% . An increasing trend was observed till 2008 (29% up to 63.8%) followed by a sharp decline observed in 2010 and 2012 (13% and 29.5%, respectively).…”
Section: Resultsmentioning
confidence: 98%
“…A large number of studies have been reported mainly from Turkey and Iran. The overall prevalence rate reported in different provinces of Turkey during the past 10 years among young adults (≤19 years old) ranges between 13% and 64% . An increasing trend was observed till 2008 (29% up to 63.8%) followed by a sharp decline observed in 2010 and 2012 (13% and 29.5%, respectively).…”
Section: Resultsmentioning
confidence: 98%
“…Soysal et al did not report the reactogenicity profile of Avaxim 80U specifically but across all three childhood hepatitis A vaccines they assessed (Avaxim 80U, Havrix 720 and Vaqta 25). No immediate reactions were reported, and the rates of local and systemic solicited reactions did not differ between the three vaccines assessed after the first or the second vaccine injection [48]. The most commonly reported adverse event was pain (11.5% of participants).…”
Section: Safety Profile From Pooled Clinical Studies and Literature Rmentioning
confidence: 96%
“…The literature search identified 11 [39,40,[42][43][44][45][46][47][48][49][50] reports for inclusion in this review ( Figure S1). Although one article by Fisenka et al should have been excluded from this review because it assessed the use of three hepatitis A vaccines (i.e.…”
Section: Literature Identifiedmentioning
confidence: 99%
See 2 more Smart Citations